Pemberdayaan Kader Terkait Edukasi Pendampingan Keluarga Ibu Pasca Salin Melalui Buku KIA - Amalia, Rizki; Nisa, Fauziyatun; Laili, Uliyatul; Windarti, Yunik (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract (Tahoma, 9pt Bold) One of the main priorities of health development in Indonesia is maternal and child health. Post-natal care is one of the most critical stages but never gets special attention. The purpose of this community service is to increase the empowerment of cadres in the use of KIA books. This activity was carried out in Waru, Sidoarjo. The training participants were 30 cadres. In this activity, cadre empowerment was carried out to re-deliver material and train cadre mothers on how to optimize the MCH book in the postpartum section. This community service method is in the form of pre and post counseling on the use of postnatal MCH book to detect postnatal danger signs, followed by MCH book screening training using a questionnaire. The results of this community service are that the level of cadre assistance before being given education and training is mostly lacking, namely 55%, while after being given training empowerment 87%. After being given assistance, all cadres are able to understand the use and recording of the MCH book in the postpartum section, and there is a lot of health information in the MCH book. Keywords: Empowerment, postpartum, cadres, MCH book